1990
DOI: 10.1093/ije/19.3.655
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Carpal Tunnel Syndrome in Women of Childbearing Age. Findings in a Large Cohort Study

Abstract: There are few epidemiological data in the scientific literature about the carpal tunnel syndrome. This paper describes the characteristics of the 154 women referred to hospital for management of this condition among the 17,032 taking part in the Oxford-Family Planning Association contraceptive study. Standardized first referral rates for carpal tunnel syndrome doubled as age increased from 25-29 to 50 or more, tripled as smoking increased from zero to 25 or more cigarettes per day, doubled as total duration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
67
1
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 0 publications
8
67
1
1
Order By: Relevance
“…The highest incidence of CTS is among meat packers, knit underwear mills, car manufacturers, and poultry processing plants. ' 11 Vessey et al 12 found that the risk of CTS among obese women was double that of slender women and we'0 found a 250% increase in risk of a median mononeuropathy among obese compared with slender subjects.…”
mentioning
confidence: 58%
“…The highest incidence of CTS is among meat packers, knit underwear mills, car manufacturers, and poultry processing plants. ' 11 Vessey et al 12 found that the risk of CTS among obese women was double that of slender women and we'0 found a 250% increase in risk of a median mononeuropathy among obese compared with slender subjects.…”
mentioning
confidence: 58%
“…It is surprising that the multivariate analyses did not identify a significant association between smoking and disability following any of the back disorders or carpal tunnel syndrome, given the substantial literature associating smoking with the incidence (though not necessarily the development of disability) of these conditions [Frymoyer et al, 1980;Svensson et al, 1983;Kelsey et al, 1984;Owen and Damron, 1984;Biering-Sørensen and Thomsen, 1986;Saraste and Hultman, 1987;Battié et al, 1989;Deyo and Bass, 1989;Vessey et al, 1990;Heliövarra et al, 1991;Tsai et al, 1992;Boshuizen et al, 1993;O'Connor and Marlowe, 1993;Reynolds et al, 1994;Finkelstein, 1995;Nathan et al, 1996;Tanaka et al, 1997]. Perhaps there are many more causal pathways and mediating factors for back disorders that dilute the effect of smoking.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of the strength of the causal relation was based on the review of 11 epidemiological studies that consistently showed strong associations between occupational exposure and CTS with evidence of a temporal association. Uncertainty remains however, about the fraction of CTS that is attributable to work.…”
mentioning
confidence: 99%